The cook's herb garden - Cox, Jeff , 1940-; Moine, Marie-Pierre (Dorling Kindersley, 2010)
With a catalog of 150 different culinary herbs and their varieties, more than 30 recipes, step-by-step photographs on how to plant, nurture, harvest, and store herbs, and flavor charts that list the best herbs to partner with popular ingredients, "The Cook's Herb Garden" is an ideal reference